WARPPLS APPLICATION FOR MARKETING MIX ANALYSIS OF CONSUMER LOYALTY WITH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE AT PT BALI LUXE TRADA, BALI - Lestari, Diah Ayu; Satoto, Eko Budi; Nursaidah, Nursaidah (Univesitas Muhammadiyah Tangerang, 2024)
This study aims to determine and analyze the effect of the 4P marketing mix (product, price, location, and promotion) on customer loyalty with customer satisfaction as an intervening variable at PT Bali Luxe Trada, Bali. This type of research uses quantitative research methods with the population in the study, namely customers of PT Bali Luxe Trada. The sampling method used was purposive sampling using the calculation of the slovin formula of 120 respondents of PT Bali Luxe Trada. Data collection techniques include questionnaires and documentation. Hypothesis testing is done by variance-based SEM or Partial Least Square (SEM-PLS) testing with the help of the WarpPLS 8.0 program through descriptive analysis, outer model testing, inner model, and hypothesis testing. The results of the analysis obtained show that partially the variables of product, price, location have a positive and significant effect on customer loyalty and customer satisfaction. Promotions have a positive but not significant effect on customer loyalty or customer satisfaction. While on indirect influences, only product variables have a significant effect on customer loyalty through customer satisfaction of PT Bali Luxe Trada, Bali.